Enhancing Photoluminescence: Photonic Bound States in the Continuum in Si Structures with the Self‐Assembled Ge Nanoislands (Laser Photonics Rev. 15(7)/2021). Issue 7 (7th July 2021) - Dyakov, Sergey A.; Stepikhova, Margarita V.; Bogdanov, Andrey A.; Novikov, Alexey V.; Yurasov, Dmitry V.; Shaleev, Mikhail V.; Krasilnik, Zakhary F.; Tikhodeev, Sergei G.; Gippius, Nikolay A.
Abstract : The cover image illustrates the photonic crystal slab's eigenmode as demonstrated in article number 2000242 by Sergey Dyakov and co‐workers. The cones represent the rotation of the electric vector during one period of electromagnetic oscillations. From this figure, one can determine the symmetry type of this mode and predict the features of the far‐field emissivity of quantum emitters at the corresponding frequency.